Juridical Review of the Criminal Act of Car Theft by Rental Car Mode According to the Criminal Law (KUHP) - Horas Sahatma Hatuaon; Soerya Respationo; Erniyanti Erniyanti (International Journal of Education and Literature, 2024)
Transportation is very important for our daily lives when we want to travel. Rental cars are one of the current solutions when we don’t have a vehicle. However, the convenience provided by car rental is often misused by irresponsible parties. Starting from damaged returns, theft and embezzlement. The research carried out by researchers is Empirical Juridical legal research which is research that directly obtains data in the field. By doing research in the field, researchers will understand better and be able to find out more clearly the actual events related to the title of the research being studied. From the results of this research, the author can conclude that one of the modus operandi of embezzlement in the jurisdiction of the Riau Islands Regional Police is the crime of embezzlement and/or fraud and/or malicious assistance. This way the car is rented and then pawned to someone else without the knowledge of the original owner of the car. For this reason, the police have two efforts to overcome this, namely by preventive and repressive methods. The police’s obstacles in uncovering cases are two factors, namely internal and external factors. The suggestions put forward in this research are the need to increase the budget in the context of investigating and investigating criminal acts of embezzlement of rental cars, providing education to car rental businesses to install GPS to increase car security and providing more telescopic services for rental cars.